0487 Comparing Three Home Sleep Apnea Testing Devices to Polysomnography: Evaluating Diagnostic Rates for Obstructive Sleep Apnea. (27th April 2018) - Arguelles, J; Kim, J; Becker, K; Chang, J; Dewitte, J; Montoya, E; Villalpando, C; Woodrum, R; Henry, L; Takehara, J; Hwang, D
Abstract: Introduction: We separately reported excellent agreement for respiratory parameters between 3 Home sleep Apnea Testing(HSAT) devices and polysomnography(PSG). This study compares diagnostic rates based on real-world clinical protocols. Methods: Patients were eligible if referred to Kaiser Permanente Sleep Center(Fontana, CA) for suspected OSA and HSAT-appropriate. Participants wore three HSAT devices simultaneously for three nights: Device "A"(ARES; SleepMed, Inc); Device "N"(Nox T-3; Nox Medical); Device "W"(WatchPAT, Itamar Medical). Nights 1(N1) and 2(N2) were performed at home; Night 3(N3) was performed simultaneously with PSG. Sensitivities/specificities and diagnostic rates were calculated based on REI4%(HSAT) and AHI4%(PSG). Results: 60(30 men, 30 women; 46.4 ± 11.8 years) patients enrolled; 57 completed N3 testing with PSG. Sensitivity/Specificity of diagnosing OSA(REI/AHI≥5) for 1 night study(HSAT N3 versus PSG) were "A" 97/75%, "N" 92/65%, "W" 97/57% and diagnosing moderate-severe OSA(REI/AHI≥15) were "A" 88/97%, "N" 92/90%, "W" 96/100%. Diagnostic Rates for OSA/moderate-severe OSA for PSG were 70/47%. HSAT on the same night(N3) demonstrated similar diagnostic rates: "A" 76/43%, "N" 75/48%, "W" 82/48%. When taking the highest REI from the 3 HSAT nights(N1-3), rates increased to: "A" 86/58%, "N" 82/57%, "W" 88/58%.We then modeled after real-world protocols by identifying those with a "negative" HSAT on N1(REI<5) and determined the % of subsequent studies that would turn "positive"(REI≥5) depending on type of study performed(PSG; HSAT N3; highest of HSAT N1-3): "A"(27%; 27%; 47%); "N"(25%; 25%; 47%); "W"(33%; 40%; 53%). We also identified those with a HSAT N1 REI<15 and determined the % of subsequent studies that would turn "positive" for moderate-severe OSA: "A"(22%; 16%; 22%); "N"(16%; 16%; 16%); "W"(13%; 10%; 17%). Overall, diagnostic rates were comparable or higher when follow-up HSAT versus PSG was performed. Conclusion: HSAT diagnostic rates are comparable to PSG, and multi-night protocol can further increase the yield. When HSAT results are "negative", it may be appropriate to repeat HSAT instead of PSG when pre-test probability for OSA is high. Support (If Any): None.